Evaluation of a latex agglutination assay for the identification of Burkholderia pseudomallei and Burkholderia mallei. - Duval, B; Elrod, MG; Gee, J; Chantratita, N; Tandhavanant, S; Limmathurotsakul, D; Hoffmaster, A (American Society of Tropical Medicine and Hygiene, 2014)
Cases of melioidosis and glanders are rare in the United States, but the etiologic agents of each disease (Burkholderia pseudomallei and Burkholderia mallei, respectively) are classified as Tier 1 select agents because of concerns about their potential use as bioterrorism agents. A rapid, highly sensitive, and portable assay for clinical laboratories and field use is required. Our laboratory has further evaluated a latex agglutination assay for its ability to identify B. pseudomallei and B. mallei isolates. This assay uses a monoclonal antibody that specifically recognizes the capsular polysaccharide produced by B. pseudomallei and B. mallei, but is absent in closely related Burkholderia species. A total of 110 B. pseudomallei and B. mallei were tested, and 36 closely related Burkholderia species. The latex agglutination assay was positive for 109 of 110 (99.1% sensitivity) B. pseudomallei and B. mallei isolates tested.